1999
DOI: 10.2527/1999.7782201x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of spermatozoa and seminal plasma on leukocyte migration into the uterus of gilts.

Abstract: Yorkshire x Landrace gilts were used to determine the effect of spermatozoa and seminal plasma on postbreeding uterine leukocyte influx. Estrus detection was performed with a boar at 12-h intervals following synchronization with 400 IU eCG and 200 IU of hCG. All gilts were AI once, 24 h after the detection of estrus following random assignment to a 2x2x3 factorial arrangement of treatments (sperm or sperm-free AI doses), AI dose medium (seminal plasma or PBS), and lavage time following AI. Gilts were treated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
64
1
3

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(73 citation statements)
references
References 0 publications
5
64
1
3
Order By: Relevance
“…In the present study, the number of non-phagocytosed frozen-thawed spermatozoa (10 6-7 cells) recovered from the uterus was lower than that in the previous study of fresh spermatozoa (10 7-8 cells) [7]. Seminal plasma-free medium has been shown to induce a post-breeding inflammatory response in gilts in the form of an influx of PMNs into the uterine lumen that persists for more than 36 h [3]. Therefore, most of frozen-thawed spermatozoa seem to be phagocytosed due to the induced uterine inflammation after the first AI.…”
Section: Discussioncontrasting
confidence: 39%
See 1 more Smart Citation
“…In the present study, the number of non-phagocytosed frozen-thawed spermatozoa (10 6-7 cells) recovered from the uterus was lower than that in the previous study of fresh spermatozoa (10 7-8 cells) [7]. Seminal plasma-free medium has been shown to induce a post-breeding inflammatory response in gilts in the form of an influx of PMNs into the uterine lumen that persists for more than 36 h [3]. Therefore, most of frozen-thawed spermatozoa seem to be phagocytosed due to the induced uterine inflammation after the first AI.…”
Section: Discussioncontrasting
confidence: 39%
“…The backflow of semen and phagocytosis of spermatozoa by polymorphonuclear leukocytes (PMNs) appear to be the two main mechanisms responsible for the reduction in the amount of spermatozoa [2]. In gilts, although the influx of PMNs into the uterus can persist for as long as 36 h after insemination, the number of uterine spermatozoa and the clearance time from the uterus are highly dependent on the presence or absence of seminal plasma [3]. It has been shown that seminal plasma inhibits neutrophil chemotaxis in vitro [4] and protects spermatozoa from an inflamed uterine environment, resulting in improved fertility [5,6].…”
mentioning
confidence: 99%
“…Several factors can explain the success of intrauterine insemination. First, the deposition of semen in the body of the uterus or uterine horns reduces the possibility of losing the sperm through polymorphonuclear leukocyte phagocytosis (15,16). Secondly, there is little or no loss of spermatozoa caused by semen backflow from the female reproductive system, which quite often happens immediately after intracervical insemination (8,17).…”
Section: Discussionmentioning
confidence: 99%
“…Dilution reduces the protein content and natural antioxidants, as well as other natural ingredients of seminal plasma necessary for normal functioning and the integrity of the sperm cell membrane (1,25,26). Additionally, seminal plasma plays an important role in regulating capacitation, the establishment of an oviductal sperm reservoir (27), the modulation of the uterine immune response (15), and sperm transport in the female genital tract, as well as in gamete interaction and fusion (28)(29)(30).…”
Section: Discussionmentioning
confidence: 99%
“…These studies show that SP-induced inflammation is greatest 5 days after treatment and in some cases still evident up to 9 days following SP infusion. Conversely, it has been shown that sperm alone can increase luminal leukocytes and when sperm is administered in conjunction with SP a reduction in luminal leukocytes is observed within 36 h of treatment (Rozeboom et al 1999).…”
Section: Sp Signaling and Porcine Reproductionmentioning
confidence: 99%